Doctors' approaches to decision support in counseling patients with localized prostate cancer: an Asian perspective - Cheong, Ai Theng; Lee, Ping Yein; Ng, Chirk Jenn; Lee, Yew Kong; Ong, Teng Aik; Abdullah, Khatijah Lim; Abdul Razack, Azad Hassan (Penerbit Universiti Kebangsaan Malaysia, 2016)
There are many treatment options for localized prostate cancer, and there is clinical equipoise in relation to the treatment outcomes. This study aimed to explore doctors’ approaches to decision support in counselling patients with localized prostate cancer in a country with a less established system of support and care delivery for cancer treatment. Four in-depth interviews and three focus group discussions were conducted with seven government policy makers/consultant urologists, three oncologists, four private urologists and six urology trainees in Malaysia between 2012 and 2013. Doctors facilitated the treatment decision by explaining about the disease and the treatment options, which included monitoring, side effects and complications of each treatment option. Paper-based (charts and diagram drawings) or electronic (ipad apps and websites) illustrations and physical models were used as patient education aids. Further reading materials and websites links were often provided to patients. Patients were given time till subsequent follow up to decide on the treatment and family involvement was encouraged. Referral to other healthcare professionals (oncologist, radiotherapist or other urologist) for second opinion was offered to the patients. The doctors would recommend patients to speak to prostate cancer survivors for peer support but official support groups were not easily accessible. This study highlighted a multi-faceted approach to support patients with localized prostate cancer in making a treatment decision. It not only involved the doctors (urologist or oncologist) themselves, but also empowered the patients and their social network to support the decision making process.